Flexible electromagnetic shielding material with heat conduction and sensing properties and preparation method and application thereof
By constructing a 'coco tree' structure with polydopamine coated silica/silver nanowires and nanocellulose, the problem of performance compatibility of electromagnetic shielding materials is solved, and the versatility of efficient electromagnetic shielding, heat conduction and sensing is achieved. Provides high-performance solutions for flexible electronic devices.
Patent Information
- Application Number
- CN202411522737.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-10-29
AI Technical Summary
The existing electromagnetic shielding materials are difficult to compatible with high electromagnetic shielding performance and lightness, sensing and thermal conductivity, and cannot meet the application needs of flexible electronic equipment.
Polydopamine-coated silica combined with silver nanowires are used to construct the 'coco tree' structure through chelation, and cross-link glutaraldehyde and nanocellulose to form a stable network structure to achieve efficient electromagnetic shielding, thermal conductivity and strain transmission Take into account both feelings.
It has achieved high electromagnetic shielding performance, excellent thermal conductivity and sensitive strain sensing performance, which meets the use needs of portable intelligent electronic devices, and has a simple and economical preparation process, and has good industrial development prospects.
Smart Images

Figure CN119161640A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electromagnetic shielding, and in particular relates to a flexible electromagnetic shielding material having both thermal conductivity and sensing performance, and a preparation method and application thereof. Background Art
[0002] With the rapid development of modern communication equipment, the adverse effects of electromagnetic radiation have become increasingly prominent, such as interfering with information, interrupting communications, causing equipment failures, and even endangering health. In recent years, the rapid popularization of flexible electronic products and portable devices has urgently required electromagnetic shielding materials to shift to lightweight and thin materials on the basis of high shielding performance; in addition, when the equipment is running, heat will accumulate inside. If the heat cannot be dissipated in time, it will seriously affect the accuracy and service life of the equipment.
[0003] At present, it is increasingly important for flexible electronic devices to have strain sensing capabilities, which can not only broaden the application scope of flexible electronics in bio-monitoring, wearable devices, smart skin and other fields, but also provide the possibility for achieving real-time monitoring with high sensitivity and high reliability. However, the shielding effectiveness of existing electromagnetic shielding materials is generally low, and the high electromagnetic shielding performance of the materials is incompatible with lightness, thinness, sensing and thermal conductivity, and can no longer meet the application requirements of flexible electronic devices. Therefore, it is urgent to develop electromagnetic shielding materials with high shielding, thermal conductivity and sensing performance. Summary of the invention
[0004] In response to the technical problems existing in the prior art, the present invention provides a flexible electromagnetic shielding material with both thermal conductivity and sensing properties, and a preparation method and application thereof, so as to solve the technical problems that the shielding effectiveness of existing electromagnetic shielding materials is generally low and the high electromagnetic shielding performance of the material is incompatible with the lightness, thinness, sensing and thermal conductivity.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is: The present invention provides a method for preparing a flexible electromagnetic shielding material having both thermal conductivity and sensing performance, comprising: Adding the polydopamine-coated silica dispersion to the silver nanowire dispersion, and mixing by magnetic stirring, so that the polydopamine-coated silica is combined with the silver nanowires through chelation, to obtain a polydopamine-coated silica / silver nanowire dispersion; After the nanocellulose dispersion and the polydopamine-coated silica / silver nanowires are dispersed and mixed, ultrasonic treatment is first performed, and then glutaraldehyde is added to react with the amino group of the polydopamine and the hydroxyl group of the nanocellulose to form a Schiff base bond, and then mechanical stirring is performed to obtain a polydopamine-coated silica / silver nanowire / nanocellulose dispersion; The polydopamine-coated silica / silver nanowire / nanocellulose dispersion is subjected to vacuum filtration and drying treatment to obtain the flexible electromagnetic shielding material with both thermal conductivity and sensing performance.
[0006] Furthermore, the preparation process of the polydopamine-coated silica dispersion is as follows: The silica dispersion liquid and the dopamine dispersion liquid are mixed and subjected to magnetic stirring treatment, so that a coating layer is formed on the surface of the silica through the self-polymerization reaction of dopamine to obtain a polydopamine-coated silica dispersion liquid.
[0007] Furthermore, the preparation process of the silver nanowire dispersion is as follows: Dissolve silver nitrate in ethylene glycol to obtain solution A; Dissolving polyvinyl pyrrolidone and ferric chloride hexahydrate in ethylene glycol to obtain solution B; The B solution and the A solution are mixed and stirred evenly to react. After the reaction is completed, impurities are removed by centrifugation to obtain the silver nanowire dispersion.
[0008] Furthermore, a polydopamine-coated silica dispersion is added to a silver nanowire dispersion to form a mixed system b; the solid phase composition of the mixed system b includes: a polydopamine-coated silica with a mass fraction of 42wt%-78wt% and a silver nanowire with a mass fraction of 22wt%-58wt%.
[0009] Furthermore, the nanocellulose dispersion and the polydopamine-coated silica / silver nanowires are dispersed and mixed, and glutaraldehyde is added to form a mixed system c; the solid phase composition of the mixed system c includes: nanocellulose with a mass fraction of 21.5wt%-44.5wt%, polydopamine-coated silica / silver nanowires with a mass fraction of 55wt%-76wt% and glutaraldehyde with a mass fraction of 0.5wt%-2.5wt%.
[0010] Furthermore, during ultrasonic treatment, the ultrasonic power is 300-700 W, and the ultrasonic time is 5-25 min.
[0011] Furthermore, in the process of mechanical stirring, the stirring speed is 200-600 rpm and the stirring time is 30-150 min.
[0012] The present invention also provides a flexible electromagnetic shielding material having both thermal conductivity and sensing properties, characterized in that the flexible electromagnetic shielding material having both thermal conductivity and sensing properties is prepared by using the flexible electromagnetic shielding material having both thermal conductivity and sensing properties.
[0013] Furthermore, the absolute electromagnetic shielding effectiveness of the flexible electromagnetic shielding material having both thermal conductivity and sensing performance is 13277.5-15303.1 dB·cm 2 ·g -1 .
[0014] The present invention also provides an application of a flexible electromagnetic shielding material having both thermal conductivity and sensing performance. The flexible electromagnetic shielding material having both thermal conductivity and sensing performance is applied to flexible electronic devices.
[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a method for preparing a flexible electromagnetic shielding material with both thermal conductivity and sensing performance. The method comprises the following steps: combining polydopamine-wrapped silica with silver nanowires through chelation, and utilizing the metal chelation of polydopamine to construct a firm "cocoa tree" structure, thereby obtaining a polydopamine-coated silica / silver nanowire dispersion having a "cocoa tree" structure. Secondly, glutaraldehyde reacts with the amino group of polydopamine and the hydroxyl group of nanocellulose to form a Schiff base bond to enhance the interaction. In addition, the nanocelluloses are interwoven to form a stable network structure to construct a film having a structure similar to a "cocoa tree", thereby achieving the purpose of taking into account both efficient electromagnetic shielding, thermal conductivity and strain sensing. The flexible electromagnetic shielding material prepared by the present invention meets the use requirements of portable intelligent electronic devices. Compared with existing electromagnetic shielding materials, the flexible electromagnetic shielding material has higher electromagnetic shielding performance, excellent thermal conductivity and sensitive strain sensing performance, thereby providing favorable technical support for the commercialization of electromagnetic shielding materials. In addition, the preparation process of the flexible electromagnetic shielding material is simple, economical and efficient, and has good prospects for industrial development. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is a surface morphology of the flexible electromagnetic shielding material with both thermal conductivity and sensing performance prepared in Example 4; Figure 2 This is a surface morphology of the polydopamine-coated silica / silver nanowires prepared in Example 4; Figure 3 This is a diagram showing the flexibility of the flexible electromagnetic shielding material having both thermal conductivity and sensing properties prepared in Example 4; Figure 4 This is a graph of electromagnetic shielding effectiveness of the flexible electromagnetic shielding material having both thermal conductivity and sensing performance prepared in Examples 1-5; Figure 5 This is a graph of thermal conductivity of the flexible electromagnetic shielding material having both thermal conductivity and sensing performance prepared in Examples 1-5; Figure 6 This is a graph of the current signal generated when writing on the flexible electromagnetic shielding material with both thermal conductivity and sensing properties prepared in Example 4. DETAILED DESCRIPTION
[0017] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail in the following specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0018] The present invention provides a method for preparing a flexible electromagnetic shielding material having both thermal conductivity and sensing performance, comprising the following steps: Step 1, mixing a silica dispersion and a dopamine dispersion, and subjecting the mixture to a magnetic stirring treatment at a rotation speed of 200-600 rpm for 4-8 hours to form a coating layer on the surface of the silica through a self-polymerization reaction of dopamine, thereby obtaining a polydopamine-coated silica dispersion; wherein, after mixing the silica dispersion and the dopamine dispersion, a mixed system a is formed; and the solid phase composition in the mixed system a includes: a mass fraction of 40wt%-80wt% of silica and a mass fraction of 20wt%-60wt% of dopamine.
[0019] Step 2, dissolving silver nitrate in ethylene glycol to obtain solution A; dissolving polyvinyl pyrrolidone and ferric chloride hexahydrate in ethylene glycol to obtain solution B; mixing solution B with solution A and stirring them evenly to react, and after the reaction is completed, removing impurities by centrifugation to obtain the silver nanowire dispersion.
[0020] Step 3, adding the polydopamine-coated silica dispersion to the silver nanowire dispersion, and mixing by magnetic stirring so that the polydopamine-coated silica combines with the silver nanowires through chelation to obtain a polydopamine-coated silica / silver nanowire dispersion; wherein, after the polydopamine-coated silica dispersion is added to the silver nanowire dispersion, a mixed system b is formed; the solid phase composition in the mixed system b includes: a mass fraction of 42wt%-78wt% of polydopamine-coated silica and a mass fraction of 22wt%-58wt% of silver nanowires; the magnetic stirring speed is 200-600rpm, and the magnetic stirring time is 30-150min.
[0021] Step 4, disperse and mix the nanocellulose dispersion and the polydopamine-coated silica / silver nanowires, first perform ultrasonic treatment at an ultrasonic power of 300-700W for 5-25min; then add glutaraldehyde to react with the amino group of glutaraldehyde and the hydroxyl group of nanocellulose to form a Schiff base bond; then, mechanically stir at a rotation speed of 200-600rpm for 30-150min to obtain a polydopamine-coated silica / silver nanowire / nanocellulose dispersion.
[0022] Among them, the nanocellulose dispersion and the polydopamine-coated silica / silver nanowires are dispersed and mixed, and glutaraldehyde is added to form a mixed system c; the solid phase composition in the mixed system c includes: nanocellulose with a mass fraction of 21.5wt%-44.5wt%, polydopamine-coated silica / silver nanowires with a mass fraction of 55wt%-76wt% and glutaraldehyde with a mass fraction of 0.5wt%-2.5wt%.
[0023] Step 5: vacuum filter and dry the polydopamine-coated silica / silver nanowire / nanocellulose dispersion to obtain the flexible electromagnetic shielding material with both thermal conductivity and sensing properties; wherein the drying temperature during the drying process is 25-65°C.
[0024] Preparation principle: The present invention provides a method for preparing a flexible electromagnetic shielding material having both thermal conductivity and sensing performance. The polydopamine-coated silica dispersion is added to the silver nanowire dispersion so that the polydopamine-coated silica is combined with the silver nanowires through chelation, and the metal chelation of polydopamine is used to construct a strong "cocoa tree" structure to obtain a polydopamine-coated silica / silver nanowire dispersion with a "cocoa tree" structure; wherein the silica particles serve as the "cocoa fruit" in the "cocoa tree" structure, and the silver nanowires serve as the "branches" in the "cocoa tree" structure; then, the nanocellulose dispersion and the polydopamine-coated silica / silver nanowire dispersion are mixed and ultrasonically treated, and glutaraldehyde is added to form a Schiff base bond through the reaction of glutaraldehyde with the amino group of polydopamine and the hydroxyl group of nanocellulose to enhance the interaction; in addition, the nanocellulose dispersion and the polydopamine-coated silica / silver nanowire dispersion are mixed and ultrasonically treated, and then ... The rice cellulose is interwoven to form a stable network structure to construct a film with a "cocoa tree" structure, so as to obtain a flexible electromagnetic shielding material with both thermal conductivity and sensing properties; the "cocoa tree" structure constructed in the present invention has a complete conductive and thermal conductive path, which effectively guarantees the sensing and thermal conductivity of the material; at the same time, the multi-components induce multiple interface polarizations to extend the electromagnetic wave loss path and enhance the electromagnetic shielding effectiveness; secondly, the silicon dioxide embedded in the "cocoa tree" structure can improve impedance matching and provide good mechanical support for the silver nanowire conductive network; in summary, the flexible electromagnetic shielding material can achieve the purpose of high-efficiency electromagnetic shielding, thermal conductivity and strain sensing; the preparation process is simple, economical and efficient, and has good prospects for industrial development.
[0025] Compared with the existing electromagnetic shielding materials, the flexible electromagnetic shielding material prepared by the present invention has higher electromagnetic shielding performance, excellent thermal conductivity and sensitive strain sensing performance, meets the use requirements of electromagnetic shielding materials in portable intelligent electronic devices, and provides favorable technical support for the commercialization of electromagnetic shielding materials; wherein, the absolute electromagnetic shielding effectiveness of the flexible electromagnetic shielding material is 13277.5-15303.1dB·cm 2 ·g -1 The plane thermal conductivity is 3.96-4.39W / m·k, and at -8×10 -11 ~26×10 -11 It has sensitive strain sensing performance in the current range of μA.
[0026] Example 1 This embodiment 1 provides a method for preparing a flexible electromagnetic shielding material having both thermal conductivity and sensing performance, comprising the following steps: Step 1, adding a silica dispersion and a dopamine dispersion into a magnetic stirrer, mixing, and magnetically stirring at a rotation speed of 200 rpm for 4 hours to obtain a polydopamine-coated silica dispersion; wherein, after the silica dispersion and the dopamine dispersion are mixed, a mixed system a is formed; the solid phase composition in the mixed system a includes: a mass fraction of 40wt% silica and a mass fraction of 60wt% dopamine.
[0027] Step 2, dissolving silver nitrate in ethylene glycol to obtain solution A; dissolving polyvinyl pyrrolidone and ferric chloride hexahydrate in ethylene glycol to obtain solution B; mixing solution B with solution A and stirring evenly, reacting in an environment of 160° C.; after the reaction is completed, centrifuging to remove impurities to obtain the silver nanowire dispersion.
[0028] Step 3, adding the polydopamine-coated silica dispersion to the silver nanowire dispersion, and mixing by magnetic stirring so that the polydopamine-coated silica combines with the silver nanowires through chelation to obtain a polydopamine-coated silica / silver nanowire dispersion; wherein, after the polydopamine-coated silica dispersion is added to the silver nanowire dispersion, a mixed system b is formed; the solid phase composition in the mixed system b includes: a polydopamine-coated silica with a mass fraction of 42wt% and a silver nanowire with a mass fraction of 58wt%; the magnetic stirring speed is 200rpm, and the magnetic stirring time is 30min.
[0029] Step 4, disperse and mix the nanocellulose dispersion and the polydopamine-coated silica / silver nanowires, and first perform ultrasonic treatment at an ultrasonic power of 300 W for 5 minutes; then add glutaraldehyde to react with the amino group of glutaraldehyde and the hydroxyl group of nanocellulose to form a Schiff base bond; then, mechanically stir at a rotation speed of 200 rpm for 30 minutes to obtain a polydopamine-coated silica / silver nanowire / nanocellulose dispersion.
[0030] Among them, the nanocellulose dispersion and the polydopamine-coated silica / silver nanowires are dispersed and mixed, and glutaraldehyde is added to form a mixed system c; the solid phase composition in the mixed system c includes: nanocellulose with a mass fraction of 44.5wt%, polydopamine-coated silica / silver nanowires with a mass fraction of 55wt% and glutaraldehyde with a mass fraction of 0.5wt%.
[0031] Step 5: vacuum filter and dry the polydopamine-coated silica / silver nanowire / nanocellulose dispersion to obtain the flexible electromagnetic shielding material with both thermal conductivity and sensing properties; wherein the drying temperature during the drying process is 25°C.
[0032] Example 2 This embodiment 2 provides a method for preparing a flexible electromagnetic shielding material having both thermal conductivity and sensing performance, comprising the following steps: Step 1, adding a silica dispersion and a dopamine dispersion into a magnetic stirrer, mixing, and magnetically stirring at a rotation speed of 300 rpm for 5 hours to obtain a polydopamine-coated silica dispersion; wherein, after the silica dispersion and the dopamine dispersion are mixed, a mixed system a is formed; the solid phase composition in the mixed system a includes: a mass fraction of 50wt% silica and a mass fraction of 50wt% dopamine.
[0033] Step 2: prepare a silver nanowire dispersion; the preparation method of the silver nanowire dispersion is exactly the same as the process of step 2 in the above embodiment 1, and will not be repeated here.
[0034] Step 3, adding the polydopamine-coated silica dispersion to the silver nanowire dispersion, and mixing by magnetic stirring so that the polydopamine-coated silica combines with the silver nanowires through chelation to obtain a polydopamine-coated silica / silver nanowire dispersion; wherein, after the polydopamine-coated silica dispersion is added to the silver nanowire dispersion, a mixed system b is formed; the solid phase composition in the mixed system b includes: a polydopamine-coated silica with a mass fraction of 59wt% and a silver nanowire with a mass fraction of 41wt%; the magnetic stirring speed is 300rpm, and the magnetic stirring time is 60min.
[0035] Step 4, disperse and mix the nanocellulose dispersion and the polydopamine-coated silica / silver nanowires, and first perform ultrasonic treatment at an ultrasonic power of 400 W for 10 min; then add glutaraldehyde to react with the amino group of glutaraldehyde and the hydroxyl group of nanocellulose to form a Schiff base bond; then, mechanically stir at a rotation speed of 300 rpm for 60 min to obtain a polydopamine-coated silica / silver nanowire / nanocellulose dispersion.
[0036] Among them, the nanocellulose dispersion and the polydopamine-coated silica / silver nanowires are dispersed and mixed, and glutaraldehyde is added to form a mixed system c; the solid phase composition in the mixed system c includes: nanocellulose with a mass fraction of 36wt%, polydopamine-coated silica / silver nanowires with a mass fraction of 63wt% and glutaraldehyde with a mass fraction of 1.0wt%.
[0037] Step 5: vacuum filter and dry the polydopamine-coated silica / silver nanowire / nanocellulose dispersion to obtain the flexible electromagnetic shielding material with both thermal conductivity and sensing properties; wherein the drying temperature during the drying process is 35°C.
[0038] Example 3 This embodiment 3 provides a method for preparing a flexible electromagnetic shielding material having both thermal conductivity and sensing performance, comprising the following steps: Step 1, adding a silica dispersion and a dopamine dispersion into a magnetic stirrer, mixing, and magnetically stirring at a rotation speed of 400 rpm for 6 hours to obtain a polydopamine-coated silica dispersion; wherein, after the silica dispersion and the dopamine dispersion are mixed, a mixed system a is formed; the solid phase composition in the mixed system a includes: a mass fraction of 60wt% of silica and a mass fraction of 40wt% of dopamine.
[0039] Step 2: prepare a silver nanowire dispersion; the preparation method of the silver nanowire dispersion is exactly the same as the process of step 2 in the above embodiment 1, and will not be repeated here.
[0040] Step 3, adding the polydopamine-coated silica dispersion to the silver nanowire dispersion, and mixing by magnetic stirring so that the polydopamine-coated silica combines with the silver nanowires through chelation to obtain a polydopamine-coated silica / silver nanowire dispersion; wherein, after the polydopamine-coated silica dispersion is added to the silver nanowire dispersion, a mixed system b is formed; the solid phase composition in the mixed system b includes: polydopamine-coated silica with a mass fraction of 68wt% and silver nanowires with a mass fraction of 32wt%; the magnetic stirring speed is 400rpm, and the magnetic stirring time is 90min.
[0041] Step 4, the nanocellulose dispersion and the polydopamine-coated silica / silver nanowires are dispersed and mixed, and firstly ultrasonically treated at an ultrasonic power of 500 W for 15 min; then glutaraldehyde is added to react the glutaraldehyde with the amino group of the polydopamine and the hydroxyl group of the nanocellulose to form a Schiff base bond; then, mechanical stirring is performed at a rotation speed of 400 rpm for 90 min to obtain a polydopamine-coated silica / silver nanowire / nanocellulose dispersion.
[0042] Among them, the nanocellulose dispersion and the polydopamine-coated silica / silver nanowires are dispersed and mixed, and glutaraldehyde is added to form a mixed system c; the solid phase composition in the mixed system c includes: nanocellulose with a mass fraction of 29.5wt%, polydopamine-coated silica / silver nanowires with a mass fraction of 69wt% and glutaraldehyde with a mass fraction of 1.5wt%.
[0043] Step 5: vacuum filter and dry the polydopamine-coated silica / silver nanowire / nanocellulose dispersion to obtain the flexible electromagnetic shielding material with both thermal conductivity and sensing properties; wherein the drying temperature during the drying process is 45°C.
[0044] Example 4 This embodiment 4 provides a method for preparing a flexible electromagnetic shielding material having both thermal conductivity and sensing performance, comprising the following steps: Step 1, adding a silica dispersion and a dopamine dispersion into a magnetic stirrer, mixing, and magnetically stirring at a rotation speed of 500 rpm for 7 hours to obtain a polydopamine-coated silica dispersion; wherein, after the silica dispersion and the dopamine dispersion are mixed, a mixed system a is formed; the solid phase composition in the mixed system a includes: a silica mass fraction of 70wt% and a dopamine mass fraction of 30wt%.
[0045] Step 2: prepare a silver nanowire dispersion; the preparation method of the silver nanowire dispersion is exactly the same as the process of step 2 in the above embodiment 1, and will not be repeated here.
[0046] Step 3, adding the polydopamine-coated silica dispersion to the silver nanowire dispersion, and mixing by magnetic stirring so that the polydopamine-coated silica combines with the silver nanowires through chelation to obtain a polydopamine-coated silica / silver nanowire dispersion; wherein, after the polydopamine-coated silica dispersion is added to the silver nanowire dispersion, a mixed system b is formed; the solid phase composition in the mixed system b includes: polydopamine-coated silica with a mass fraction of 74wt% and silver nanowires with a mass fraction of 26wt%; the magnetic stirring speed is 500rpm, and the magnetic stirring time is 120min.
[0047] Step 4, the nanocellulose dispersion and the polydopamine-coated silica / silver nanowires are dispersed and mixed, and firstly ultrasonically treated at 600W for 20min; then glutaraldehyde is added to react the glutaraldehyde with the amino group of polydopamine and the hydroxyl group of nanocellulose to form a Schiff base bond; then, mechanical stirring is performed at a rotation speed of 500rpm for 120min to obtain a polydopamine-coated silica / silver nanowire / nanocellulose dispersion.
[0048] Among them, the nanocellulose dispersion and the polydopamine-coated silica / silver nanowires are dispersed and mixed, and glutaraldehyde is added to form a mixed system c; the solid phase composition in the mixed system c includes: nanocellulose with a mass fraction of 25wt%, polydopamine-coated silica / silver nanowires with a mass fraction of 73wt% and glutaraldehyde with a mass fraction of 2.0wt%.
[0049] Step 5: vacuum filter and dry the polydopamine-coated silica / silver nanowire / nanocellulose dispersion to obtain the flexible electromagnetic shielding material with both thermal conductivity and sensing properties; wherein the drying temperature during the drying process is 55°C.
[0050] Example 5 This embodiment 5 provides a method for preparing a flexible electromagnetic shielding material having both thermal conductivity and sensing performance, comprising the following steps: Step 1, adding a silica dispersion and a dopamine dispersion into a magnetic stirrer, mixing, and magnetically stirring at a rotation speed of 600 rpm for 8 hours to obtain a polydopamine-coated silica dispersion; wherein, after the silica dispersion and the dopamine dispersion are mixed, a mixed system a is formed; the solid phase composition in the mixed system a includes: 80 wt% silica by mass and 20 wt% dopamine by mass.
[0051] Step 2: prepare a silver nanowire dispersion; the preparation method of the silver nanowire dispersion is exactly the same as the process of step 2 in the above embodiment 1, and will not be repeated here.
[0052] Step 3, adding the polydopamine-coated silica dispersion to the silver nanowire dispersion, and mixing by magnetic stirring so that the polydopamine-coated silica combines with the silver nanowires through chelation to obtain a polydopamine-coated silica / silver nanowire dispersion; wherein, after the polydopamine-coated silica dispersion is added to the silver nanowire dispersion, a mixed system b is formed; the solid phase composition in the mixed system b includes: polydopamine-coated silica with a mass fraction of 78wt% and silver nanowires with a mass fraction of 22wt%; the magnetic stirring speed is 600rpm, and the magnetic stirring time is 150min.
[0053] Step 4, the nanocellulose dispersion and the polydopamine-coated silica / silver nanowires are dispersed and mixed, and firstly ultrasonically treated at 700W for 25min; then glutaraldehyde is added to react the glutaraldehyde with the amino group of polydopamine and the hydroxyl group of nanocellulose to form a Schiff base bond; then, mechanical stirring is performed at a rotation speed of 600rpm for 150min to obtain a polydopamine-coated silica / silver nanowire / nanocellulose dispersion.
[0054] Among them, the nanocellulose dispersion and the polydopamine-coated silica / silver nanowires are dispersed and mixed, and glutaraldehyde is added to form a mixed system c; the solid phase composition in the mixed system c includes: nanocellulose with a mass fraction of 21.5wt%, polydopamine-coated silica / silver nanowires with a mass fraction of 76wt% and glutaraldehyde with a mass fraction of 2.5wt%.
[0055] Step 5: vacuum filter and dry the polydopamine-coated silica / silver nanowire / nanocellulose dispersion to obtain the flexible electromagnetic shielding material with both thermal conductivity and sensing properties; wherein the drying temperature during the drying process is 65°C.
[0056] As attached Figure 1 As shown, attached Figure 1 The surface morphology of the flexible electromagnetic shielding material with both thermal conductivity and sensing performance prepared in Example 4 is given in the figure; Figure 1 It can be seen that the surface of the flexible electromagnetic shielding material prepared in Example 4 shows the phenomenon of polydopamine-coated silica / silver nanowires interweaving in nanocellulose, and the polydopamine-coated silica / silver nanowires are dispersed by the nanocellulose network to form a uniform conductive and thermal conductive path, which is beneficial to improve the electromagnetic shielding effectiveness by reducing conductivity loss.
[0057] As attached Figure 2 As shown, attached Figure 2 The surface morphology of the polydopamine-coated silica / silver nanowires prepared in Example 4 is given in FIG. Figure 2 It can be seen that the prepared polydopamine-coated silica / silver nanowires have silica particles adhered to the surface of the silver nanowires, forming a structure similar to a "cocoa tree", which can combine conductivity loss and polarization loss with internal multiple scattering and scattering to effectively improve the electromagnetic shielding effectiveness.
[0058] As attached Figure 3 As shown, attached Figure 3 The flexible performance display diagram of the flexible electromagnetic shielding material with both thermal conductivity and sensing performance prepared in Example 4 is given in the figure; Figure 3 It can be seen that the flexible electromagnetic shielding material prepared in Example 4 has good flexibility.
[0059] As attached Figure 4 As shown, attached Figure 4 The electromagnetic shielding effectiveness diagrams of the flexible electromagnetic shielding materials with both thermal conductivity and sensing performance prepared in Examples 1-5 are given in the attached Figure 4 It can be seen that the flexible electromagnetic shielding materials prepared in Examples 1-5 all have excellent electromagnetic shielding performance; specifically, when the thickness of the flexible electromagnetic shielding material prepared in Example 1 is 71 μm, the electromagnetic shielding effectiveness of the material reaches 67.74 dB, and its absolute electromagnetic shielding effectiveness is calculated to be 14189.6 dB·cm 2 ·g -1 When the thickness of the flexible electromagnetic shielding material prepared in Example 2 is 67 μm, the electromagnetic shielding effectiveness of the material reaches 70.67 dB, and its absolute electromagnetic shielding effectiveness is calculated to be 13609.5 dB·cm 2 ·g -1 When the thickness of the flexible electromagnetic shielding material prepared in Example 3 is 63 μm, the electromagnetic shielding effectiveness of the material reaches 74.05 dB, and its absolute electromagnetic shielding effectiveness is calculated to be 14494.2 dB·cm 2 ·g -1 When the thickness of the flexible electromagnetic shielding material prepared in Example 4 is 59 μm, the electromagnetic shielding effectiveness of the material reaches 76.91 dB, and its absolute electromagnetic shielding effectiveness is calculated to be 15303.1 dB·cm 2 ·g -1 When the thickness of the flexible electromagnetic shielding material prepared in Example 5 is 54 μm, the electromagnetic shielding effectiveness of the material reaches 71.17 dB, and its absolute electromagnetic shielding effectiveness is calculated to be 13277.5 dB·cm 2 ·g -1 It can be seen that the flexible electromagnetic shielding materials prepared in Examples 1-5 all meet the requirements of portable electronic devices for electromagnetic shielding materials that are light, thin, and efficient.
[0060] As attached Figure 5 As shown, attached Figure 5 The thermal conductivity diagram of the flexible electromagnetic shielding material with both thermal conductivity and sensing performance prepared in Examples 1-5 is given in the attached Figure 5It can be seen that the planar thermal conductivity of the flexible electromagnetic shielding material prepared in Example 1 is 4.39 W / (m·k), the planar thermal conductivity of the flexible electromagnetic shielding material prepared in Example 2 is 4.31 W / (m·k), the planar thermal conductivity of the flexible electromagnetic shielding material prepared in Example 3 is 4.24 W / (m·k), the planar thermal conductivity of the flexible electromagnetic shielding material prepared in Example 4 is 4.15 W / (m·k), and the planar thermal conductivity of the flexible electromagnetic shielding material prepared in Example 5 is 4.39 W / (m·k), all of which can quickly realize heat transfer and improve the heat management capability of electronic equipment.
[0061] As attached Figure 6 As shown, attached Figure 6 The figure shows the current signal generated when writing the flexible electromagnetic shielding material with both thermal conductivity and sensing properties prepared in Example 4; specifically, Figure A is the current signal generated when writing the letter A, Figure B is the current signal generated when writing the letter B, and Figure C is the current signal generated when writing the letter C.
[0062] From the attached Figure 6 It can be seen that when the local strain of the prepared flexible electromagnetic shielding material changes, the corresponding current signal will also change. When the same letter is written repeatedly, the generated electrical signal remains basically consistent; when different letters are written, the external stresses are different and different changes are shown. It can be seen that the flexible electromagnetic shielding material prepared in Example 5 has high sensitivity and continuous and stable strain sensing performance, and has great application value in the fields of flexible electronics, medical health, etc.
[0063] The present invention aims to solve the problems of existing electromagnetic shielding materials being thin and light, having high electromagnetic shielding effectiveness, and not taking into account both sensing and thermal conductivity. The present invention utilizes the metal chelation effect of polydopamine, takes silicon dioxide as the "cocoa fruit", and silver nanowires as the "branches" to construct a firm "cocoa tree" structure - polydopamine-coated silicon dioxide / silver nanowires, which are then cross-linked with nanocellulose through glutaraldehyde, and nanocellulose is interwoven to form a stable network structure to form an electromagnetic shielding film with a structure similar to the "cocoa tree"; by constructing the "cocoa tree" structure, impedance matching is improved, the electromagnetic wave loss path is extended, a "resistance-capacitance circuit" is formed, multiple interface polarizations are induced, and polarization losses are generated; at the same time, a complete conductive and thermal conductive path is formed, so as to realize a multifunctional electromagnetic shielding film with high-efficiency electromagnetic shielding, thermal conductivity and strain sensing, and provide a new strategy for the research and development of high-performance and multifunctional integrated new electromagnetic shielding materials.
[0064] The electromagnetic shielding effectiveness of the flexible electromagnetic shielding material with both thermal conductivity and sensing performance prepared by the present invention is 76.91 dB, the planar thermal conductivity is 4.15 W / (m·k), the current signal changes accordingly when different letters are written, and it has high sensitivity and continuous and stable strain sensing performance, achieving lightness, flexibility, high electromagnetic shielding effectiveness, excellent thermal conductivity and sensitive sensing performance; the preparation process is simple, the operation process is safe, and it has the potential and technical feasibility of industrial-scale production.
[0065] The above embodiment is only one of the implementation methods that can realize the technical solution of the present invention. The scope of protection claimed by the present invention is not limited only to this embodiment, but also includes changes, replacements and other implementation methods that can be easily thought of by any technician familiar with the technical field within the technical scope disclosed by the present invention.
Claims
1. A method for preparing a flexible electromagnetic shielding material having both thermal conductivity and sensing properties, characterized in that: include: adding a polydopamine-coated silica dispersion to a silver nanowire dispersion and mixing the mixture by magnetic stirring so that the polydopamine-coated silica binds to the silver nanowires through chelation to obtain a polydopamine-coated silica / silver nanowire dispersion; After the nanocellulose dispersion and the polydopamine-coated silica / silver nanowires are dispersed and mixed, ultrasonic treatment is first performed, and then glutaraldehyde is added to react with the amino groups of the glutaraldehyde and the hydroxyl groups of the nanocellulose to form Schiff base bonds, and then mechanical stirring is performed to obtain a polydopamine-coated silica / silver nanowire / nanocellulose dispersion; The polydopamine-coated silica / silver nanowire / nanocellulose dispersion is subjected to vacuum filtration and drying treatment to obtain the flexible electromagnetic shielding material with both thermal conductivity and sensing properties.
2. The method for preparing a flexible electromagnetic shielding material having both thermal conductivity and sensing properties according to claim 1, characterized in that: The preparation process of polydopamine-coated silica dispersion is as follows: The silicon dioxide dispersion and the dopamine dispersion are mixed and subjected to magnetic stirring treatment, so that a coating layer is formed on the surface of the silicon dioxide through the self-polymerization reaction of dopamine to obtain a polydopamine-coated silicon dioxide dispersion.
3. The method for preparing a flexible electromagnetic shielding material having both thermal conductivity and sensing properties according to claim 1, characterized in that: The preparation process of silver nanowire dispersion is as follows: Dissolve silver nitrate in ethylene glycol to obtain solution A; Dissolve polyvinyl pyrrolidone and ferric chloride hexahydrate in ethylene glycol to obtain solution B; The B solution and the A solution are mixed and stirred uniformly, and then reacted. After the reaction is completed, impurities are removed by centrifugation to obtain the silver nanowire dispersion.
4. The method for preparing a flexible electromagnetic shielding material having both thermal conductivity and sensing properties according to claim 1, characterized in that: After adding the polydopamine-coated silica dispersion to the silver nanowire dispersion, a mixed system b is formed; the solid phase composition of the mixed system b includes: a mass fraction of 42wt%-78wt% of polydopamine-coated silica and a mass fraction of 22wt%-58wt% of silver nanowires.
5. The method for preparing a flexible electromagnetic shielding material having both thermal conductivity and sensing properties according to claim 1, characterized in that: The nanocellulose dispersion and the polydopamine-coated silica / silver nanowires are dispersed and mixed, and glutaraldehyde is added to form a mixed system C; the solid phase composition of the mixed system C includes: nanocellulose with a mass fraction of 21.5wt%-44.5wt%, polydopamine-coated silica / silver nanowires with a mass fraction of 55wt%-76wt%, and glutaraldehyde with a mass fraction of 0.5wt%-2.5wt%.
6. The method for preparing a flexible electromagnetic shielding material having both thermal conductivity and sensing properties according to claim 1, characterized in that: During ultrasonic treatment, the ultrasonic power is 300-700W and the ultrasonic time is 5-25min.
7. The method for preparing a flexible electromagnetic shielding material having both thermal conductivity and sensing properties according to claim 1, characterized in that: During the mechanical stirring process, the stirring speed is 200-600 rpm and the stirring time is 30-150 min.
8. A flexible electromagnetic shielding material having both thermal conductivity and sensing properties, characterized in that: The flexible electromagnetic shielding material having both thermal conductivity and sensing properties is prepared by using the flexible electromagnetic shielding material having both thermal conductivity and sensing properties as described in claims 1-7.
9. A flexible electromagnetic shielding material having both thermal conductivity and sensing properties according to 8, characterized in that: The absolute electromagnetic shielding effectiveness of the flexible electromagnetic shielding material with both thermal conductivity and sensing performance is 13277.5-15303.1dB·cm 2 ·g -1 .
10. Use of a flexible electromagnetic shielding material having both thermal conductivity and sensing properties as claimed in claim 8 or 9, characterized in that: The flexible electromagnetic shielding material having both thermal conductivity and sensing properties is applied in flexible electronic devices.
Citation Information
Patent Citations
Flexible composite electromagnetic shielding film constructed by utilizing conductive nanofibers and preparation method thereof
CN113265908A
Full-color developing flexible printing material and preparation method thereof
CN113481605A
Preparation method of flexible regenerated carbon fiber cellulose-based electromagnetic shielding film and product thereof
CN113667159A
Flexible composite film with electromagnetic shielding performance and thermal conductivity as well as preparation method and application of flexible composite film
CN117384428A
Rubber-coated glass assembly
CN118769838A
